P034 Smoking status, primary adult occupation and risk of recurrent urothelial bladder carcinoma: data from the cancer genome atlas (TCGA) project. (1st September 2016) - Wilcox, Amber; Silverman, Debra; Friesen, Melissa; Locke, Sarah; Russ, Daniel; Hyun, Noorie; Colt, Joanne; Figueroa, Jonine; Rothman, Nat; Moore, Lee; Koutros, Stella
Abstract : Tobacco smoking and occupational exposures are the leading risk factors for urothelial bladder carcinoma (UBC) incidence, yet little is known about the contribution of these two major risk factors for UBC recurrence. We evaluated whether smoking status and primary adult occupation are associated with time to UBC recurrence for patients with muscle-invasive bladder cancer submitted to The Cancer Genome Atlas (TCGA) project. Of 406 cases, 358 patients had data on recurrence and time to recurrence, of which 133 (37.2%) experienced a recurrence. Kaplan-Meier and Cox proportional hazard methods were used to assess the association between smoking status, employment in a high-risk occupation for bladder cancer, occupational diesel exhaust exposure, and 2010 Standard Occupational Classification (SOC) group and time to UBC recurrence. Current smokers who smoked for more than 40 pack-years had an increased risk of recurrence compared to never smokers (HR 2.1, 95% CI: 1.1, 4.1). Additionally, employment in a high-risk occupation was associated with a shorter time to recurrence (log-rank P = 0.005). We found an increased risk of recurrence for those employed in occupations with probable diesel exhaust exposure (HR: 1.7, 95% CI: 1.0, 2.8) and for those employed in production occupations (HR: 2.0, 95% CI: 1.1, 3.6). This study suggests smoking status impacts risk of UBC recurrence, although several previous studies provided mixed evidence of this association. In addition, while there is a known causal relationship between occupation and bladder cancer risk, our study suggests that occupation may also be related to increased risk of recurrence.